Perceptions of staff and students about the NC(V) model of workplace Engineering artisan training offered by South African TVET colleges - Du Plooy, B.; Du Preez, K. (South African Journal of Higher Education, 2022)
Vocational training is a contentious issue in South Africa, where large per centages are regularly cited for unemployment statistics, and in particular for youth and post-school unemployment. Vocational study programmes at Technical and Vocational Education and Training (TVET) colleges are often seen as one possible remedy to these problems. The Department of Higher Education and Training’s (DHET) long-term objective is to increase the number of learners that will qualify as artisans, which represent a major scarce/critical skills area in South Africa. However, the throughput and certification rates of TVET students are disconcertingly low, with National Certificate (Vocational) (NC(V)) Engineering courses regularly cited as having some of the lowest rates. This article reports on a small research study on the perceptions of TVET staff and students about NC(V) Engineering programmes, conducted at two TVET colleges in South Africa. Qualitative and quantitative methods were used to collect data from NC(V) Engineering students and lecturers. The most important findings of the study include that there is a critical collaboration gap between industry and the TVET sector and that both NC(V) staff and students experience the need for addressing the (im)balance of time spent on practical versus theoretical training as part of NC(V) programmes. A clear understanding of the perceptions and concerns of TVET NC(V) Engineering lecturers and students may assist in addressing issues locally, at individual TVET colleges, and globally, at national policy and Sector Education and Training Authority (SETA) level, that could in future serve to contribute to improved academic performance, including higher throughput and certification rates, of NC(V) Engineering students.